2017
DOI: 10.20344/amp.7712
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Anthropometrics and Physical Fitness of Young Portuguese School-Aged Children

Abstract: RESUMOIntrodução: Analisar as tendências seculares ao nível da antropometria e aptidão física das crianças portuguesas. Material e Métodos: Um grupo de 1819 crianças (881 rapazes e 938 raparigas) entre os 10 e os 11 anos de idade, foi avaliado no 5º e 6º ano de escolaridade durante 20 anos. A ANCOVA foi usada para analisar as variações de antropometria (índice de massa corporal, peso e altura) e aptidão física (sentar e alcançar, força abdominal, salto horizontal e corrida de velocidade) durante quatro quinqué… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 19 publications
9
62
1
1
Order By: Relevance
“…A majority of the studies monitoring muscular fitness trends over time have focused on children. Most of these studies show a decreasing trend in muscular fitness, although, similar to the present study findings, no changes have also been observed, while one study reported an increase . Furthermore, the mean sit‐up results were 37 reps/min for 18‐20 years Finnish men and 34‐38 repetitions in present 5‐10 years older study sample.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A majority of the studies monitoring muscular fitness trends over time have focused on children. Most of these studies show a decreasing trend in muscular fitness, although, similar to the present study findings, no changes have also been observed, while one study reported an increase . Furthermore, the mean sit‐up results were 37 reps/min for 18‐20 years Finnish men and 34‐38 repetitions in present 5‐10 years older study sample.…”
Section: Discussionsupporting
confidence: 83%
“…Most of these studies show a decreasing trend in muscular fitness, 10,11,[21][22][23] although, similar to the present study findings, no changes have also been observed, 24,25 while one study reported an increase. 26 Furthermore, the mean sit-up results were 37 reps/ min for 18-20 years Finnish men 7 and 34-38 repetitions in present 5-10 years older study sample. Similarly, the mean push-up performance varied between 31 and 33 reps./min in the study by Santtila et al, 7 whereas the range of mean values was 24-29 in the present study.…”
Section: Discussionmentioning
confidence: 53%
“…The magnitudes of these secular increases were broadly comparable in magnitude to those reported in other European children over the past two decades 7,9 . The combination of increases in both measures provide evidence for an overall increase in body size for children of this age which is evident from the year-olds from this affluent area 11 .…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, temporal trends in muscular fitness of Dutch [69], Finnish [40], Mozambican [21], New Zealand [1], Portuguese [18] and Welsh [75] youth appear to be more stable, with sex-specific or test-specific differences on selected outcomes. For example, over a 20-year study period involving Mozambican youth the handgrip strength of females decreased whereas males increased their handgrip strength [21].…”
Section: Temporal Trends In Muscular Fitnessmentioning
confidence: 72%